Pengaruh Sikap Pekerja dalam Theory of Planned Behavior terhadap Kepatuhan Keselamatan dan Kesehatan Kerja di Pabrik Minyak Kelapa Sawit - Yusmaini, Yusmaini; Ginting, Chrismis Novalinda; Chiuman, Linda (LPPM Hang Tuah Pekanbaru, 2025)
Occupational Health and Safety (OHS) is a crucial factor in the palm oil mill industry, which has a high risk of workplace accidents. The Theory of Planned Behavior (TPB) provides a framework for understanding how workers' attitudes, risk awareness, and commitment to safety behavior influence compliance with safety procedures and the reduction of workplace accidents.This study aims to analyze the influence of workers' attitudes, risk awareness, and commitment to safety behavior on safety compliance and accident reduction in palm oil mills. A quantitative cross-sectional approach was used, with 200 respondents from palm oil mill workers. Data were collected through questionnaires and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS 4.0 to examine the relationships between variables.The results show that positive worker attitudes significantly influence safety procedure compliance (path coefficient = 0.323, p < 0.05) and accident reduction (path coefficient = 0.303, p < 0.05). Risk awareness has a significant effect on safety procedure compliance (path coefficient = 0.218, p < 0.05) and accident reduction (path coefficient = 0.223, p < 0.05). Furthermore, commitment to safety behavior positively influences safety procedure compliance (path coefficient = 0.248, p < 0.05) and accident reduction (path coefficient = 0.343, p < 0.05). The research model demonstrated R² values of 0.456 for compliance and 0.556 for accident reduction, indicating a moderate influence.